The Effect of Pandemic Covid-19 into Internship Activity of Mojokerto Vocational High Schools - Setiyawan, Andri; Kurniawan, Arief (Universitas Ahmad Dahlan, 2021)
This study aims to determine what steps were taken by the Vocational High School (SMK) 1 Mojokerto in implementing Dual System Education / Internship which is a mandatory activity for high school students to improve students` insights and qualities and foster good relations between a vocational high school and a job provider company during the COVID-19 pandemic. This research is qualitative research that aims to describe the implementation of Dual System Education / Internship by Vocational high School 1 Mojokerto during the COVID-19 pandemic.Â The Effect of Pandemic Covid-19 into Internship Activity on apprenticeship: 1) During the pandemic, halt the internship process; internship operations can resume after the pandemic has passed. (2) Relocating student street vendors to businesses that follow government and corporation laws and require the use of personal protective equipment (PPE). (3) Internships will be phased out in favor of online learning.